Pertentangan Hak Pengelolaan Lahan (HPL) dan Hak Ulayat : Implikasi PP 18 Tahun 2021 - Harianti, Isnin; Rato, Dominikus; Dwi Anggono, Bayu (Pamulang Law Review, 2024)
This article explores the conflict between Land Management Rights (HPL) and Customary Rights and analyzes its implications in the context of Government Regulation (PP) 18/2021 in Indonesia. The analytical focus encompasses the origins of the conflict, its details within the legal framework, and the identification of root issues that trigger field tensions. The research methodology involves legal document analysis, case studies, and interviews with relevant stakeholders. The study also evaluates the impact of the implementation of PP 18/2021 on the conflict and its implications in legal, social, and environmental dimensions. The research findings provide crucial insights for policymakers, stakeholders, and the community, supporting the understanding of the HPL and Customary Rights conflict and seeking sustainable solutions. Critical analysis underscores the necessity for a review of existing regulations to accommodate the traditional rights of local communities, preserve environmental sustainability, and reduce the potential for conflict within a more inclusive legal framework.